Essays on Brecht Theater and Politics - Mews, Siegfried; Knust, Herbert (UNC Studies in the Germanic Languages and Literatures, 1974)
These essays represent the push to provide interdisciplinary Brecht research to English-speaking audiences following his death in 1956 and offer novel readings of his works indicative of the major literary questions of the time. The essays explore both Brecht's theoretical approach and political thought, with many also taking a comparative approach to analysis of individual plays. The contributors are Reinhold Grimm, Karl-Heinz Schoeps, Herbert Knust, Hans Meyer, Siegfried Mews, Raymond English, James Lyon, Darko Suvin, Gisela Bahr, Grace Allen, Ralph Ley, John Fuegi, Andrzej Wirth and David Bathrick.